Association of HLA Genotype With T-Cell Activation in Human Immunodeficiency Virus (HIV) and HIV/Hepatitis C Virus–Coinfected Women - Kovacs, Andrea A Z; Kono, Naoko; Wang, Chia-Hao; Wang, Daidong; Frederick, Toni; Operskalski, Eva; Tien, Phyllis C; French, Audrey L; Minkoff, Howard; Kassaye, Seble; T. Golub, Elizabeth; Aouizerat, Bradley E; et al. (The Journal of infectious diseases, 2020)
Abstract Background Global immune activation and HLA alleles are each associated with the pathogenesis of human immunodeficiency virus (HIV) and hepatitis C virus . Methods We evaluated the relationship between 44 HLA class I and 28 class II alleles and percentages of activated CD8 (CD8+CD38+DR+) and CD4 (CD4+CD38+DR+) T cells in 586 women who were naive to highly active antiretroviral therapy. We used linear generalized estimating equation regression models, adjusting for race/ethnicity, age, HIV load, and hepatitis C virus infection and controlling for multiplicity using a false discovery rate threshold of 0.10. Results Ten HLA alleles were associated with CD8 and/or CD4 T-cell activation. Lower percentages of activated CD8 and/or CD4 T cells were associated with protective alleles B*57:03 (CD8 T cells, −6.6% [P = .002]; CD4 T cells, −2.7% [P = .007]), C*18:01 (CD8 T cells, −6.6%; P < .0008) and DRB1*13:01 (CD4 T cells, −2.7%; P < .0004), and higher percentages were found with B*18:01 (CD8 T cells, 6.2%; P < .0003), a detrimental allele. Other alleles/allele groups associated with activation included C*12:03, group DQA1*01:00, DQB1*03:01, DQB1*03:02, DQB1*06:02, and DQB1*06:03. Conclusion These findings suggest that a person’s HLA type may play a role in modulating T-cell activation independent of viral load and sheds light on the relationship between HLA, T-cell activation, immune control, and HIV pathogenesis. We found that specific HLA alleles predict CD8 and CD4 T-cell activation, independent of HLA associations with viral load. These findings suggest that host genetic variation could affect risk for end-organ diseases through an immune activation mechanism.